Bogoo: Warisan Perahu Komuniti Bajau Laut di Sabah, Malaysia (Bogoo: The Boat Heritage of the Bajau Laut in Sabah, Malaysia) - Ismail Ali , (Kajian Malaysia, 2007)
The Bajau Laut (Samal) people, also known as pala’u, is among the Bajau ethnic tribes in the east coast of Sabah who are still practicing the sea nomads lifestyle. They are synonym with the lepa-lepa, a boat in which they live on the sea. In the effort to preserve this heritage and culture, the Ministry of Culture, Arts and Tourism of Sabah has gazette the “Lepa-Lepa Regatta” in the Sabah tourism calendar. Other than Lepa-Lepa, the Bajau Laut community actually treasures another sampan design that is unique only to the tribe. It is the winged sampan called bogoo that is used for fishing. Nevertheless, this unique heritage and culture has never been exposed to the public by any scholar studying this subject. This article is written for the purpose of documenting the sampan as one of the heritage and culture of the Bajau Laut community in order to avoid the disappearance of this culture to the development. This writing is based on the field work done by the author regarding the tradition of Bajau Laut community in the east coast of Sabah in Mac 2007.